Meet Josefina : an American girl - Tripp, Valerie, 1951-; Tibbles, Jean-Paul; McAliley, Susan (Middleton, WI : Pleasant Co., 1997)
Nine-year-old Josefina, the youngest of four sisters living in New Mexico in 1824, tries to help run the household after her mother dies. (Gr. 2-6)
"Book one"--P. [1] of cover.
Accelerated Reader AR
Keywords: Ranch life -- New Mexico -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Sisters -- Juvenile fiction; Aunts -- Juvenile fiction; New Mexico -- History -- To 1848 -- Juvenile fiction